Theorizing commensality discourses: food truck communication and influence in local culture - Combs, Mitch, author; Aoki, Eric, advisor; Khrebtan-Hörhager, Julia, committee member; Elkins, Evan, committee member; Carolan, Michael, committee member (Colorado State University. Libraries, 2022)
Food trucks offer spaces of commensality where people negotiate cultural identity and senses of place though practices, tastes, and performances communicated through enactments of food sharing. In this dissertation, I theorize commensality as a rhetorical texture of subcultural ideology, a rhetorical texture of resistance to cultural gentrification, and as a digital process of online community building. I use rhetorical criticism and ethnographic methods of participant observation to analyze physical spaces of food truck commensality in Fort Collins, Colorado: The FOCO Food Truck Rally and North College Avenue. Additionally, I conduct a media discourse analysis of the Fort Collins food truck Instagram community. Overall, I argue that commensality operates as a subcultural ideology resistant and reifying of gourmet elitism, a rhetoric of difference resistant to cultural gentrification, and a process digital commensality building community through social mediated branding, networking, and audiencing.
Keywords: ethnography; global; rhetoric; food studies; commensality; local